Penerapan Model Pembelajaran Discovery Learning untuk Meningkatkan Hasil Belajar IPA pada Siswa Kelas V - Cahyani, Marina Rizki Tri (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
The purpose of the study was to improve science learning outcomes in the symbiotic material. The research method is classroom action research (learning improvement) with two cycles, namely cycle I and cycle II. Data collection techniques using learning outcomes tests. The data analysis technique used is descriptive quantitative with presentile data analysis. Based on the improvement of learning cycle I and cycle II, the learning outcomes of cycle I can be presented which can achieve completeness as many as 19 students (66.00%) with a class average of 71.1. Cycle II learning outcomes that can achieve completeness are 27 students (93.1%) with a class average of 84.1. Judging from the percentage of completeness and the average value of increasing learning outcomes, it can be concluded that the use of the discovery learning model in the symbiotic material can significantly improve learning outcomes.